PENGGUNAAN APLIKASI PERHITUNGAN STRUKTUR SRRP (SUMATERA REGION ROAD PROJECT) IBRD LOAD NO. 4307-IND UNTUK DINDING PENAHAN TANAH PADA TEBING SUNGAI JEMBATAN CIDERES - NABILAH (Universitas Majalengka, 2021)
The retaining wall of the river cliff is an important part of the bridge's abutment defense and minimizes the avalanche around the river cliffs. The type of earth retaining wall mounted on the cideres bridge district is the type of gravity. Planning on this retaining wall using SRRP (SUMATERA REGION ROAD PROJECT) IBRD LOAD NO. 4307-IND which includes data in the form of dimensions, land heap data, basic soil data, earthquake load data, and security figures with output issued in the form of vertical, horizontal, rolling moments, anchoring and voltage moments. With a high dimension of 3,00m slope of 20 degrees of the ground resulting in a safety figure against the roll and slide greater than the requirement of 2.20, the maximum pressure turned out to be smaller than the carrying capacity of the permit so that it meets the requirements of 91.73 kN/m2 < 120 kN/m2 and the positive voltage value on the piece indicates the compressive voltage. The minimum voltage that occurs turns out to be greater than 0, which means that in piece 1 all the voltages that occur are pressed so that it meets the requirements.